Future Wireless and Optical Networks Networking Modes and Cross-Layer Design - Jiang, Shengming; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2012)
As the number of smart-phone applications and users continues to grow, the future Internet must integrate both optical wired networks and mobile wireless networks in order to meet the demands for pervasive computing and network capacity. This important text/reference reviews the challenges of all-optical and wireless networks for the future Internet. With a focus on cross-layer design and optimization, the book proposes a number of modifications to existing layered reference models, in addition to discussing revisions to current end-to-end arguments. The text also examines how these approaches can enhance the energy efficiency of the network. Topics and features: Presents a thorough introduction to major networking modes and their effect on Internet development Proposes a new structure favorable for all-optical packet switching Discusses a new quality of service (QoS) provisioning approach, which overcomes the scalability problem of IntServ and the coarse QoS granularity of DiffServ Describes the end-to-end arguments in Internet design, before investigating a solution to congestion control problems in multi-hop wireless and all-optical networks Examines how to exploit multiple-input-multiple-output technology to improve network performance in centralized wireless networks Surveys green networking strategies from a quantitative perspective Suggests a strategic vision for possible developments of network technology for the future Internet Presenting state-of-the-art research on new networking approaches, this text is a must-read for all researchers and practitioners interested in developing technologies for next-generation applications and the future Internet.
Introduction and Overview -- Internet Development versus Networking Modes -- Two-Level Source Routing (TLSR) for All-Optical Packet Switching -- Networking with TLSR -- Differentiated Queueing Service (DQS) for Granular QoS -- Cost Model for Granular End-to-End QoS with DQS -- Quantitative End-to-End Arguments: Performance Analysis -- Quantitative End-to-End Arguments: Complexity Estimation -- Numerical Discussion of Quantitative End-to-End Arguments -- Decoupling Congestion Control from TCP: Semi-TCP -- Enabling Simultaneous MAC Transmission with MIMO: Logical MIMO -- Numerical Evaluation of MAC Schemes Based on Physical and Logical MIMO -- To Be Continued.
Keywords: Computer communication systems; Computer Communication Networks